2015
DOI: 10.1039/c5nr04097c
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward clonable inorganic nanoparticles

Abstract: Pseudomonas moraviensis stanleyae was recently isolated from the roots of the Selenium (Se) hyperaccumulator plant Stanleya pinnata. This bacterium tolerates normally lethal concentrations of SeO32− in liquid culture, where it also produces Se nanoparticles. Structure and cellular ultrastructure of the Se nanoparticles as determined by cellular electron tomography shows the nanoparticles as intracellular, of narrow dispersity, symmetrically irregular and without any observable membrane or structured protein sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 70 publications
1
46
0
Order By: Relevance
“…Many authors have reported the synthesis of SeNPs coated by organic layers mainly composed of proteins, lipids and polysaccharides. 18,60 Ni et al 61 reported the first 3D electron tomographic analysis of SeIJIV) reduction by the cells of Pseudomonas moraviensis stanleyae providing new insights into the interactions at the nanoparticle/protein interface. They identified the first polypeptide playing a major role in the reduction of SeIJIV) and formation of intracellular of SeNPs.…”
Section: Biotransformation Of Amorphous Se Nanospheres To Trigonal Sementioning
confidence: 99%
“…Many authors have reported the synthesis of SeNPs coated by organic layers mainly composed of proteins, lipids and polysaccharides. 18,60 Ni et al 61 reported the first 3D electron tomographic analysis of SeIJIV) reduction by the cells of Pseudomonas moraviensis stanleyae providing new insights into the interactions at the nanoparticle/protein interface. They identified the first polypeptide playing a major role in the reduction of SeIJIV) and formation of intracellular of SeNPs.…”
Section: Biotransformation Of Amorphous Se Nanospheres To Trigonal Sementioning
confidence: 99%
“…12 We recently reported on the ability of glutathione reductase (GSHR) to enzymatically reduce selenite (SeO 3 2-) to zerovalent red selenium in a nicotinamide adenine dinucleotide phosphate (NADPH) dependent reaction. 13 Similar, although diminished activity, was observed for the same enzyme in reducing tellurite (TeO 3 2-) to elemental Te. Our prior work identified selenite reductase activity in Pseudomonas moravenis stanleyae.…”
mentioning
confidence: 70%
“…13 We examined the GRLMR for similar behavior. Selenium particles were synthesized in vitro and were separated from the solution using centrifugation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a solution to its scarcity, Se could be recovered from industrial, secondary resources, such as effluents of flue gas desulphurisation (FGD), using cost-effective and environmental-friendly biotechnological approaches (Cordoba & Staicu 2018). Various bacterial groups can metabolise Se to generate cellular energy (i.e., Downloaded from http://iwaponline.com/bgs/article-pdf/2/1/138/740604/bgs0020138.pdf ATP) through anaerobic respiration, in parallel with the production of solid Se nanoparticles (Ni et al 2015), as displayed in Figure 2.…”
Section: Technologies and Productsmentioning
confidence: 99%